Analysis of the impact of financial education on the savings of university students in the south of Guayaquil - Álvarez, Jennifer Roxana Tumbaco; Medina, Rosa María Benites; Reyes, Johan Méndez; López-Chila, Roberto (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of financial education on the saving habits of university students in southern Guayaquil, emphasizing its role in fostering financial stability. A quantitative approach was employed, utilizing a structured survey administered to 384 students to assess their level of financial knowledge and saving practices. The study applied correlational analysis, revealing a moderate positive relationship (Pearson coefficient = 0.518, p < 0.01) between financial education and saving behavior. Findings indicate that although 69% of students have received financial education, only 50% regularly create a personal budget, highlighting gaps in financial planning. Moreover, 69% of respondents consider financial education crucial in university curricula. The study concludes that financial education significantly influences saving habits, but its effectiveness depends on external factors such as access to financial products and economic conditions. Practical implications suggest that universities should strengthen their financial education programs by incorporating structured methodologies, such as the Kakeibo method, to enhance responsible saving. Expanding these initiatives could improve students’ economic well-being and contribute to long-term financial stability.